Dual energy X‐ray beam ptycho‐fluorescence imaging. (5th October 2021) - Cipiccia, Silvia; Brun, Francesco; Di Trapani, Vittorio; Rau, Christoph; Batey, Darren J.
Abstract : A novel scheme for simultaneous X‐ray ptychographic and fluorescence imaging is presented. The method is based on a dual energy X‐ray beam, chromatic focusing optics and an energy discriminating photon counting detector. Abstract : X‐ray ptychography and X‐ray fluorescence are complementary nanoscale imaging techniques, providing structural and elemental information, respectively. Both methods acquire data by scanning a localized beam across the sample. X‐ray ptychography processes the transmission signal of a coherent illumination interacting with the sample, to produce images with a resolution finer than the illumination spot and step size. By enlarging both the spot and the step size, the technique can cover extended regions efficiently. X‐ray fluorescence records the emitted spectra as the sample is scanned through the localized beam and its spatial resolution is limited by the spot and step size. The requisites for fast ptychography and high‐resolution fluorescence appear incompatible. Here, a novel scheme that mitigates the difference in requirements is proposed. The method makes use of two probes of different sizes at the sample, generated by using two different energies for the probes and chromatic focusing optics. The different probe sizes allow to reduce the number of acquisition steps for the joint fluorescence–ptychography scan compared with a standard single beam scan, while imaging the same field of view. The new method is demonstrated experimentally using two undulator harmonics, a Fresnel zone plate and an energy discriminating photon counting detector.